Liquidity and asset pricing: evidence from the Brazilian market - Machado, Márcio André Veras (2014)
The article examines whether the two-factor model developed by Liu (2006) explains the variations in stock returns in the Brazilian market. We also compare the performance of this model with the CAPM and the three-factor model of Fama & French (1993) and investigate whether the two-factor model is robust to strategies based on size, book-to-market, momentum, earnings/price, cash flow/price, liquidity and leverage, called value anomalies. We used multiple regressions with time series to analyze the performance of the models in explaining the variations in stock returns of various portfolios. The population analyzed consisted of all the firms with shares listed on the BM&FBovespa in the period from 1995 to 2008. The two-factor model performed better than the CAPM and very near the three-factor model in terms of explanatory power. Therefore, the results obtained with the two-factor model are relevant, considering we worked with dynamic portfolios. Finally, even though the two-factor model was not able to explain some of the anomalies commonly documented in the literature, advances were evidenced, which can be considered an important step in the literature, even though much can still be accomplished.